Application of Plate on Anteromedial Surface of Humerus Through Anterolateral Approach: A Safe and Reliable Approach for Midshaft Humerus Fractures With Good Functional Outcomes - KC, Kapil Mani; GC, Raju (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND Both anterolateral and posterior plating require isolation of radial nerve while anteromedial plating does not require stripping of muscles as well as isolation of radial nerve. Moreover, anteromedial surface is smooth and flat that makes easy to apply plate even without pre-bending. The aim of our study is to assess the functional outcomes and complications after anteromedial plating through anterolateral approach for mid shaft humerus fractures. METHODS This was a descriptive analytical study conducted between 15 February 2021 to 15 May 2023. All patients of midshaft humerus fractures with age more than 18 were included in the study. Functional outcomes were assessed based on Rodriguez Merchan criteria at the time of union of fracture. Study variables included demographic profiles, mechanism of injury, type of fractures, time to unite the fracture, shoulder motion, elbow motion. RESULTS Total time required to complete the surgical procedure was 86.91±11.30 minutes (70-115 minutes). Total time required for radiological union of fracture was found to be 6.85±1.06 months (5-9 months). Forty-one (85.4%) patients had excellent functional outcomes, while 7 (14.6%) had good functional outcomes based on Rodriguez Merchan criteria at three months. All patients had excellent functional outcomes at the time of final union of fractures. CONCLUSION Anteromedial plating of mid shaft humerus fracture through anterolateral approach is technically easy, reliable, safe and free from the risk of radial nerve injury at the time of application as well as removal of plate. In addition, it does not require the release of deltoid muscle insertion which has vital role for postoperative rehabilitation.